2011
DOI: 10.1039/c0cs00114g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent heavy-metal complexes for bioimaging

Abstract: The application of phosphorescent heavy-metal complexes with d(6), d(8) and d(10) electron configurations for bioimaging is a new and promising research field and has been attracting increasing interest. In this critical review, we systematically evaluate the advantages of phosphorescent heavy-metal complexes as bioimaging probes, including their photophysical properties, cytotoxicity and cellular uptake mechanisms. The progress of research into the use of phosphorescent heavy-metal complexes for staining diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
677
1
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,173 publications
(714 citation statements)
references
References 125 publications
8
677
1
9
Order By: Relevance
“…Such an effect can be most likely ascribed to the larger molecular size of the PtL 2 Cl when compared to PtL 1 Cl, since the longer polar (i.e., triethyleneglycol) chain is expected to impart a more amphiphilic character to the complex, thus helping to cross the lipophilic cellular membranes. 20,29,30 Moreover, it has been found that the derivative bearing the NCS ligand, namely PtL 1 NCS, shows the slowest cellular internalization kinetics. Indeed, for this complex the signal observed after one minute of incubation was almost negligible and photoluminescence started to appear after five minutes, yet with low intensity.…”
Section: Bioimaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an effect can be most likely ascribed to the larger molecular size of the PtL 2 Cl when compared to PtL 1 Cl, since the longer polar (i.e., triethyleneglycol) chain is expected to impart a more amphiphilic character to the complex, thus helping to cross the lipophilic cellular membranes. 20,29,30 Moreover, it has been found that the derivative bearing the NCS ligand, namely PtL 1 NCS, shows the slowest cellular internalization kinetics. Indeed, for this complex the signal observed after one minute of incubation was almost negligible and photoluminescence started to appear after five minutes, yet with low intensity.…”
Section: Bioimaging Studiesmentioning
confidence: 99%
“…The investigation of platinum complexes for biological applications concerns mostly monomeric compounds, but aggregates show some important features as well: 19,20 (i) the emitter is shielded from the environment and in particular from dioxygen that could induce quenching; (ii) the rigidity, due to the packing of molecules in determined structures, decreases nonradiative processes; (iii) the reactivity or toxicity of the complexes is diminished by the difficult accessibility of the metal centre; (iv) changes in the excited state nature and properties lead to a bathochromic shift of excitation and emission towards more biologically interesting spectral windows and sometimes to an enhancement of the photophysical properties. In this respect, amongst all luminescent platinum derivatives, those bearing either an N^C^N 22,23 20,28,29 For this purpose, we decided to undertake a systematic study of the bio-imaging and cytotoxicity features of a series of platinum complexes bearing a N^C^N cyclometallated 1,3-di(2-pyridyl)-benzene by varying the molecular hydrophobic/hydrophilic ratio (through the introduction of ethyleneglycol moieties of different lengths) and the ancillary ligand, the incubating medium and the staining concentration. The choice of oligoethyleneglycol chains on the phosphorescent probe was based on their known ability to increase the aqueous solubility and bio-compatibility of luminescent iridium bio-labels.…”
Section: Introductionmentioning
confidence: 99%
“…The former is assigned to typical spin-allowed 1 π-π* transitions of the ligands, and the latter to LLCT and 1 MLCT transition. The band at 450 nm may be assigned to the formally spin-forbidden 3 MLCT transition. Compared to Ir(dpppz)(ppz)(ipx), the corresponding absorption bands of complex Ir(ppz) 2 (ipx) have an obvious blue-shift after the partial hydrolysis of the cyclometalated ligand, which is consistent with …”
Section: Resultsmentioning
confidence: 99%
“…Recently, there is an increasing interest in the synthesis of cyclometalated Ir(III) complexes, which have found applications as phosphors in organic light emitting diodes (OLEDs) [1], sensors [2], and luminescent labels for biomolecules [3]. At the same time, sulfurcontaining ligands, such as dithiophosphates, dithiocarbamates and dithiocarbonates, have great binding potential to metals and have a wide range of uses in coordination chemistry [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among all sensing technologies, photon‐signal‐based biosensors such as organic dyes,1, 2, 3, 4 metal complexes,5, 6, 7, 8, 9, 10 and semiconductor nanocrystals11 are the most commonly used ones. However, these probes have several limitations in detection or sensing.…”
Section: Introductionmentioning
confidence: 99%